Arithmetic, Geometry, and Coding Theory: Homage to Gilles Lachaud - Ghorpade, Sudhir R.; Ritzenthaler, Christophe; Rodier, François; Tsfasman, Michael A. (Arithmetic, Geometry, Cryptography and Coding Theory)
We give an overview of several of the mathematical works of Gilles Lachaud and provide a historical context. This is interspersed with some personal anecdotes highlighting many facets of his personality.